Covid-19 vaccines: Should we allow human challenge studies to infect healthy volunteers with SARS-CoV-2?. (9th November 2020) - McPartlin, Seán O'Neill; Morrison, Josh; Rohrig, Abie; Weijer, Charles
Abstract : The urgent need for covid-19 vaccines has prompted thousands of otherwise healthy people to volunteer to be infected with the virus to test candidate vaccines. Seán O'Neill McPartlin, Abie Rohrig, and Josh Morrison urge us to embrace the altruism of volunteers, but Charles Weijer argues that it would be dangerous and unjustified